Prevalence of toxic, compression-ischemic, diabetic and atherosclerotic polyneuropathy in primary population of the Kemerovo region - teleuts - A. V. Osipov (Scientific Сentre for Family Health and Human Reproduction Problems, 2013)
In the study based on teleuts population, which are the primary in Kemerovo region, the prevalence of toxic, compression-ischemic, diabetic and atherosclerotic polyneuropathy were determined. It was established, that the frequencies of these diseases are different depending on the sex, age, social status, profession, house site. In men population toxic polyneuropathy prevails in social group of «unemployment» of 30-39 and 40-49 years. Compression-ischemic polyneuropathy has the highest frequency in women population of 50-59 years in «unemployment» and «clerks» social groups. Diabetic and atherosclerotic polyneuropathy prevail in women population of 70 years and older and the most impairment social group is «pensioners».